Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1023/a:1008325823967
|View full text |Cite
|
Sign up to set email alerts
|

Primary gastric non-Hodgkin's lymphoma: Clinical features, management, and prognosis of 185 patients with diffuse large B-cell lymphoma

Abstract: This large series characterized the clinico-pathologic features and outcome of patients with DLCL PG-NHL. Performance status, and stage significantly influenced patient outcome. A prognostic index was developed and it identified three prognostically distinctive risk groups; however, prospective validation is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 27 publications
0
7
1
Order By: Relevance
“…Other sites of involvement have been associated with a worse prognosis, such as GI tract, respiratory system, liver, and pancreas. Several studies have reported an improved outcome in patients with gastric DLBCL , although this is likely associated with a better survival in patients with early stages. However, the prognosis in advanced stages has remained poor.…”
Section: Discussionmentioning
confidence: 99%
“…Other sites of involvement have been associated with a worse prognosis, such as GI tract, respiratory system, liver, and pancreas. Several studies have reported an improved outcome in patients with gastric DLBCL , although this is likely associated with a better survival in patients with early stages. However, the prognosis in advanced stages has remained poor.…”
Section: Discussionmentioning
confidence: 99%
“…In two recently published series of patients with primary gastric NHL, one from our institution and the other from the International Extranodal Lymphoma Study Group, the use of the IPI required modification. 28,29 Also in a large, randomized study of patients with stage I-II NHL, 87% of patients were considered low-risk according to the criteria of the IPI, and almost all patients (99%) were in the two lowest risk groups of that index. 30 Those published studies may imply that the IPI as originally proposed may lose its prognostic value if used without modification in certain groups of low-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…32 Of all tested variables in our study, only the modified IPI and the primary site (tonsil vs nontonsil) were found to prognosticate OS and EFS; however, the prognostic impact of the primary site was only minor. Modification to the original IPI was deemed necessary, and the prognostic values of those modified indices were shown in other extranodal sites 28,29 and for patients with nodal and extranodal localized NHL. 30 The site of localized extranodal lymphoma is an important independent determinant of outcome and is predictive of clinical behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, m-IPI retained their prognostic significance for shorter PFS and OS upon the Cox regression model. Previous studies (20,21) have indicated that m-IPI, in gDLBCL, is an effective prognostic factor, although it has not been reported that m-IPI at HT were adverse factors for PFS/OS. In a previous study, patients in the low-risk group (m-IPI ≤1) had significantly longer survival than intermediate/high-risk (m-IPI ≥2) patients.…”
Section: Discussionmentioning
confidence: 91%